Pandemic perspectives a filmmaker's journey in 10 essays. (OPEN AGENDA PUBLISHING, I, 2022)
Howard Burton takes us on a thought-provoking tour of a wide range of key societal issues, from biology to politics to contemporary morality, as illuminated by the COVID-19 pandemic following his involvement with a wide array of world-leading experts for his documentary, Pandemic Perspectives.